Transforming Local Governance through E-Government: Assessing the Effectiveness of Digital Sub-District Implementation - Lidya Lin Purwanti; Bambang Irawan (Universitas Muhammadiyah Gorontalo, 2025)
This study was conducted with the aim of analyzing the effectiveness of services through the implementation of digital sub-districts and identifying the support and obstacles encountered in the implementation of digital sub-districts in Sungai Keledang Sub-district, Samarinda City. This study used a qualitative method with a case study approach. The focus of this study was based on the collaboration of e-government implementation success indicators by Harvard and Moon's theory. In this study, the key informants were the sub-district head and sub-district secretary, while the informants were service staff and community members who had and had not used the digital sub-district. The data collection techniques used were observation, interviews, and documentation. The data analysis used was an interactive analysis model developed by Miles, Huberman, and Saldana. The results of the study found that the implementation of digital sub-district administration in Sungai Keledang, Samarinda City, has increased the effectiveness of public services through the acceleration of administrative processes, work efficiency of the apparatus, and ease of access to services for the community. However, this implementation still faces various obstacles, such as a lack of socialization, low digital literacy, especially among the elderly, limited network infrastructure, and application designs that are not yet fully userfriendly. Nevertheless, government policy support, the readiness of officials, and increasing digital literacy among the younger generation are significant supporting factors. These findings confirm that the success of digital subdistrict is highly dependent on the synergy between technological readiness, official support, community participation, and adaptation to local culture.